(untitled) (LEARNing Landscapes, 2023)
Emerging from the Covid-19 pandemic, a school’s teacher-leaders draw on an Interactional Ethnographic Approach to co-construct an inquiry community of Professionals Developing Professionals called Depth of Study (DOS). The study examines the three premises that undergird DOS: Making Visible the Invisible through an Interactional Ethnographic Perspective, Culture-in-the-Making, and The Over-Time Nature of Change: Periphery to Center. Through the analysis of three Telling Cases, the authors make visible how each of the three premises learned within the DOS setting affect student learning in the classroom setting.